Preterm birth prevention in twin pregnancies with progesterone, pessary, or cerclage: a systematic review and meta‐analysis. (8th February 2017) - Jarde, A; Lutsiv, O; Park, CK; Barrett, J; Beyene, J; Saito, S; Dodd, JM; Shah, PS; Cook, JL; Biringer, AB; Giglia, L; Han, Z; et al.
Abstract : Background: About half of twin pregnancies deliver preterm, and it is unclear whether any intervention reduces this risk. Objectives: To assess the evidence for the effectiveness of progesterone, cerclage, and pessary in twin pregnancies. Search strategy: We searched Medline, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, and ISI Web of Science, without language restrictions, up to 25 January 2016. Selection criteria: Randomised controlled trials of progesterone, cerclage, or pessary for preventing preterm birth in women with twin pregnancies, without symptoms of threatened preterm labour. Data collection and analysis: Two independent reviewers extracted data using a piloted form. Study quality was appraised with the Cochrane Risk of Bias tool. We performed pairwise inverse variance random‐effects meta‐analyses. Main results: We included 23 trials (all but three were considered to have a low risk of bias) comprising 6626 women with twin pregnancies. None of the interventions significantly reduced the risk of preterm birth overall at <34 or <37 weeks of gestation, or neonatal death, our primary outcomes, compared to a control group. In women receiving vaginal progesterone, the relative risk (RR) of preterm birth <34 weeks of gestation was 0.82 (95% CI 0.64–1.05, seven studies, I 2  36%), with a significant reduction in some key secondary outcomes, including very low birthweight (<1500 g, RR 0.71, 95% CI 0.52–0.98, four studies, I 2  46%) and mechanical ventilation (RR 0.61, 95% CI 0.45–0.82, four studies, I 2  22%). Conclusion: In twin gestations, although no overarching intervention was beneficial for the prevention of preterm birth and its sequelae, vaginal progesterone improved some important secondary outcomes. Tweetable abstract: Vaginal progesterone may be beneficial in twin pregnancies, but not 17‐OHPC, cerclage, or pessary. Abstract : Tweetable abstract Vaginal progesterone may be beneficial in twin pregnancies, but not 17‐OHPC, cerclage, or pessary.